1995
DOI: 10.1016/0896-6273(95)90275-9
|View full text |Cite
|
Sign up to set email alerts
|

Stable and functional expression of the CIC-3 chloride channel in somatic cell lines

Abstract: The CIC family is the superfamily of voltage-gated Cl- channels. Although the CIC channels expressed in Xenopus oocytes have been characterized, their channel properties are still poorly understood. We recently cloned a unique member of the CIC family, CIC-3, that is expressed abundantly in neurons. Its channel activity was regulated by phorbol esters. Now, we have established a stably transfected somatic cell line expressing functional CIC-3 channels and examined the CIC-3 single-channel current by patch-clam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
65
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 44 publications
4
65
0
Order By: Relevance
“…These currents displayed slight outward rectification, inactivated at positive voltages, and were sensitive to DIDS and phorbol 12,13-dibutyrate. Similar ClC-3 currents were reported by Kawasaki et al (12,20) who described rat ClC-3 currents in oocytes (20) and stably transfected CHO-K1 cells (12). Their currents exhibited somewhat different properties in the different expression systems, but they also showed only a weak outward rectification and sensitivity to DIDS as well as phorbol esters that were similar to that reported by Duan et al (11).…”
Section: Fig 2 Properties Of Endogenous Swelling-activated Currentssupporting
confidence: 76%
See 2 more Smart Citations
“…These currents displayed slight outward rectification, inactivated at positive voltages, and were sensitive to DIDS and phorbol 12,13-dibutyrate. Similar ClC-3 currents were reported by Kawasaki et al (12,20) who described rat ClC-3 currents in oocytes (20) and stably transfected CHO-K1 cells (12). Their currents exhibited somewhat different properties in the different expression systems, but they also showed only a weak outward rectification and sensitivity to DIDS as well as phorbol esters that were similar to that reported by Duan et al (11).…”
Section: Fig 2 Properties Of Endogenous Swelling-activated Currentssupporting
confidence: 76%
“…Heterologous expression of ClC-3 has been reported by two groups (11,12). These groups (11,12) observed large currents in stably transfected cell lines.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…This led to the discovery of the CLC superfamily, which includes CLC-0, CLC-1, CLC-2, CLC-3, CLCK1, CLCK2, and other channels (25,66 -70). Although there was early evidence to support the hypothesis that protein-mediating nucleotide-sensitive chloride current (P Cln ) was the ubiquitous outwardly rectifying volume-regulated Cl Ϫ channel (71), it is now believed that CLC-3, which is present in brain, kidney, and heart, among other tissues (25), is the likely molecular counterpart to volume-stimulated Cl Ϫ channels (72). RT-PCR of HIT cell mRNA, using oligonucleotide primers based on the published CLC-3 sequence, isolated a 593-bp transcript that was Ͼ90% homologous to guinea pig, rat, mouse, or human CLC-3.…”
Section: Discussionmentioning
confidence: 99%
“…ClC-2, when expressed, has been shown to display biophysical and pharmacological characteristics that differ from native VSOACs and has also been shown not to contribute to RVD (15,22). ClC-3 was originally cloned from rat kidney by Kawasaki et al (23,24), and, when expressed, currents showed basal activation and inhibition by phorbol esters and Ca 2ϩ (25,26). ClC-3 cloned from guinea pig ventricular myocytes was proposed to be the molecular candidate responsible for cardiac VSOACs (16).…”
mentioning
confidence: 99%